Signals and systems laboratory with MATLAB - Palamides, Alex; Veloni, Anastasia (CRC Press, 2014)
Introduction to MATLAB®Working EnvironmentGetting StartedMemory ManagementVectorsMatricesPlotting with MATLABComplex NumbersM-FilesInput-Output CommandsFile ManagementLogical-Relational OperatorsControl FlowSymbolic VariablesPolynomials(Pseudo)Random NumbersSignalsCategorization by the Variable TypeBasic Continuous-Time SignalsDiscrete-Time SignalsProperties of SignalsTransformations of the Time Variable for Continuous-Time SignalsTransformations of the Time Variable for Discrete-Time SignalsSystemsSystems ClassificationProperties of SystemsTime Domain System AnalysisImpulse ResponseContinuous.